Science and public understanding: the role of the historian of education. Issue 2 (4th March 2017) - Watts, Ruth
Abstract: In this article, questions of public education in both environmental issues and science, more broadly, are examined in an effort to respond to Richard Aldrich's call for historians of education to use their skills and understanding both to inform the present and to shape a more enlightened future. In particular, the lives and work of three women in science – Marianne North, Rachel Carson and Alice Stewart – are investigated through their art, writings and actions and through autobiographical and biographical material. The focus is on issues of natural history, the environment and the use and misuse of technology arising from their scientific work. In each case, how far they challenged the scientific thinking of their day or extended public understanding is explored while consideration is also made of how they were educated for their scientific careers, what impediments they faced and how far and in what ways they overcame them.